Association between alcohol consumption status and obesity-related comorbidities in men: data from the 2016 Korean community health survey - Bo-Yeon Kim; Hyewon Nam; Jeong-Ju Yoo; Yoon-Young Cho; Dug-Hyun Choi; Chan-Hee Jung; Ji-Oh Mok; Chul-Hee Kim (BMC, 2021)
Abstract Background This study was performed to investigate the association between the amount of alcohol consumption or binge drinking and obesity-related comorbidities in Korean men. Methods A total of 103,048 men aged 19 years or older were investigated in the 2016 Korean Community Health Survey. The participants were divided into five groups according to the standard number of alcoholic drinks consumed per week. Results Of the total participants, 20.7% were in the high alcohol consumption group, consuming more than 28 drinks per week. After adjustment for clinical factors, high alcohol consumption was significantly associated with higher odds ratios (ORs) of obesity (OR, 1.449; 95% confidence interval [CI], 1.412 to 1.591; P < 0.0001), hypertension (OR, 1.76; 95% CI, 1.636 to 1.894; P < 0.0001), and dyslipidemia (OR, 1.356; 95% CI, 1.247 to 1.474; P < 0.0001). In contrast, mild to moderate alcohol consumption was associated with a lower risk of diabetes (OR, 0.799; 95% CI, 0.726 to 0.88; P = 0.0015) and high alcohol consumption was not associated with a higher risk of diabetes (OR, 0.945; 95% CI, 0.86 to 1.039; P = 0.0662). Among drinkers, except for social drinkers, binge drinking was significantly associated with higher risks of obesity, hypertension, diabetes, and dyslipidemia. Conclusions High alcohol consumption was associated with higher risks of obesity, hypertension, and dyslipidemia in Korean men. In contrast, high consumption was not associated with a higher risk of diabetes. In particular, binge drinkers were associated with higher risks of obesity, hypertension, diabetes, and dyslipidemia compared to non-binge drinkers.